Histopathology of important fungal infections – A summary (Journal of Pathology of Nepal, 2019)
Fungal infections due to pathogenic or opportunistic fungi may be superficial, cutaneous, subcutaneous and systemic. With the upsurge of at risk population systemic fungal infections are increasingly common. Diagnosis of fungal infections may include several modalities including histopathology of affected tissue which reveal the morphology of fungi and tissue reaction.  Fungi can be in yeast and / or hyphae forms and tissue reactions may range from minimal to acute or chronic granulomatous inflammation. Different fungi should be differentiated from each other as well as bacteria on the basis of morphology and also clinical correlation. Special stains like GMS and PAS are helpful to identify fungi in tissue sections.